Impact of composition and salinity on swelling and gel strength of poly (acrylamide-co-acrylic acid) preformed particle gel - Ahmed Ben Ali (17792594) (2023)
The effects of various material compositions and reservoir environments on the ultimate strength and swelling kinetics of a commercial preformed particle gel (PPG) have been investigated. This study used different ratios of acrylamide and acrylic acid copolymers with a specific crosslinker concentration. Results have indicated that increasing the acrylic acid proportion enhances the PPGs’ ability to swell but weakens their network structure. In contrast, increasing the crosslinker content decreases the swelling ratio and increases the gel strength. The highest equilibrium swelling capacity among the six preformed particle gel samples was obtained for PPG2, which has the highest acrylic acid amount and the lowest crosslinker content, with a swelling ratio of 2400 g/g in deionized water and 59.8 g/g in brine 1 (67535.8 mg/l). On the contrary, PPG5, with the lowest acrylic acid and highest crosslinker content, has a swelling capacity of 239 g/g and more than 17 g/g in distilled and brine 1, respectively. Yet, PPG5 has the highest swollen gel strength of 615.5 Pa in deionized water and 3344 Pa in brine 1. The PPGs’ swelling ratios showed stepwise improvements along with increasing temperature, notably after 50 °C, yet, the storage modulus (G′) was negatively affected. The PPGs revealed the highest swelling behavior in pH 6–8, decreasing dramatically in more acidic and basic conditions. The swelling ratios of the PPGs in brine 1 at 50 °C were between 12 and 32 g/g, having strengths in the range of 566–5508 Pa, depending on the crosslinker ratio. The PPGs also demonstrated the ability to compete with other commercial PPGs as they have shown physical and thermal stability when aging at 50 °C, specifically those with high crosslinker content (PPG5). Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s42247-023-00510-2